Recent Advances in Mechanism Design for Robotics Proceedings of the 3rd IFToMM Symposium on Mechanism Design for Robotics - Bai, Shaoping; Ceccarelli, Marco (Mechanisms and Machine Science, 2015)
This volume contains the Proceedings of the 3rd IFToMM Symposium on Mechanism Design for Robotics, held in Aalborg, Denmark, 2-4 June, 2015. The book contains papers on recent advances in the design of mechanisms and their robotic applications. It treats the following topics: mechanism design, mechanics of robots, parallel manipulators, actuators and their control, linkage and industrial manipulators, innovative mechanisms/robots and their applications, among others. The book can be used by researchers and engineers in the relevant areas of mechanisms, machines and robotics.